The Role of Financial Ratios on Optimizing Company Performance At PT Angkasa Pura Retail - Umam, Fakhru; Maya Damayanti, Sylviana (Journal of Economics and Business UBS, 2023)
In the midst of a situation that is increasingly full of uncertainties, both caused by external conditions such as the global economic crisis, and the covid 19 pandemic and internal conditions such as declining financial performance and HR productivity, organizational responsiveness is needed to anticipate any changes by adapting to the business environment. changes that have the potential to create opportunities and risks for the organization, so it is important for the organization to carry out risk management. This study analyzes corporate risk, innovation capability, leverage, liquidity, and growth on company performance. Data collection is done by recording every data needed in the company's annual report. The data used is a performance report of PT. Angkasa Pura Retail which has been registered and published from 2020 to 2022. The independent variables in this study are corporate risk, innovation capability¸ leverage, liquidity, and growth and the dependent variable in this study is company performance. This study uses a quantitative approach with an explanatory or causal design. The data analysis used in this study is multiple regression with the help of the EViews 10 program. The results show that corporate risk significantly negatively affects company performance. Innovation capability, liquidity, and growth have a significant positive impact on company performance. However, leverage has no impact on company performance.